The role of emerging elites in the formation and development of communities after the fall of the Roman Empire - Tian, Yijie; Koncz, István; Defant, Sarah; Giostra, Caterina; Vyas, Deven N; Sołtysiak, Arkadiusz; Pejrani Baricco, Luisella; Fetner, Rafał; Posth, Cosimo; Brandt, Guido; Bedini, Elena; Modi, Alessandra; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2024)
Elites played a pivotal role in the formation of post-Roman Europe on both macro- and microlevels during the Early Medieval period. History and archaeology have long focused on their description and identification based on written sources or through their archaeological record. We provide a different perspective on this topic by integrating paleogenomic, archaeological, and isotopic data to gain insights into the role of one such elite group in a Langobard period community near Collegno, Italy dated to the 6-8th centuries CE. Our analysis of 28 newly sequenced genomes together with 24 previously published ones combined with isotope (Sr, C, N) measurements revealed that this community was established by and organized around a network of biologically and socially related individuals likely composed of multiple elite families that over time developed into a single extended pedigree. The community also included individuals with diverse genetic ancestries, maintaining its diversity by integrating newcomers and groups in later stages of its existence. This study highlights how shifts in political power and migration impacted the formation and development of a small rural community within a key region of the former Western Roman Empire after its dissolution and the emergence of a new kingdom. Furthermore, it suggests that Early Medieval elites had the capacity to incorporate individuals from varied backgrounds and that these elites were the result of (political) agency rather than belonging to biologically homogeneous groups.
Keywords: isotope; Humans; paleogenomics; History, Medieval; archeologie; late antiquity; Itálie; lidé; dějiny starověku; burial archaeology; mobility; římská říše; History, Ancient; Archaeology; Italy; Human Migration; Roman World; migrace lidstva; dějiny středověku